WEDDING SONGS OF THE VILLAGE OF VERKHNIY STRUTYN AND THEIR CEREMONIAL FUNCTION - Vivcharyk, Nataliia; Idushkevych, Diana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2025)
The article analyzes the wedding songs of the village of Verkhniy Strutyn, Kalush district, Ivano-Frankivsk region and the features of their performance at different stages of the wedding. It is illustrated that these folklore texts reflect the traditions, beliefs and worldview of the people, revealing a regional aspect. In analyzing wedding songs, we identified and characterized their ritual, emotional-expressive, magical, social-unifying, and entertaining functions, which they perform at various stages of the celebration – for example, during the “seating” ceremony of the bride, which involves the unbraiding of her braid and the groom’s purchase of the red ribbon woven into the hair of his future wife. Symbolic objects, images, and the magic of numbers, in particular the number three, which is often found in wedding rituals, were analyzed on occasion. The article reveals that in the village of Verkhniy Strutyn, Kalush district, Ivano-Frankivsk region, there are certain elements of ancient wedding rituals and songs that accompany them, although they are undergoing changes, they are important for preserving cultural identity in the modern multicultural space. Despite modern trends and changes caused by military events, the study of song texts accompanying weddings contributes to expanding knowledge about the regional peculiarities of Ukrainian folklore.